2019
DOI: 10.1002/jcb.28816
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of microRNA‐155 stimulates sevoflurane‐mediated cardioprotection against myocardial ischemia/reperfusion injury by binding to SIRT1 in mice

Abstract: Objective The inhaled sevoflurane has been demonstrated to protect against myocardial ischemia/reperfusion (I/R) injury. However, the relative mechanisms of sevoflurane‐mediated cardioprotection remain largely unknown. This study intends to explore the effect of miR‐155 on the sevoflurane‐mediated cardioprotection by regulating Sirtuin 1 (SIRT1) in mouse models of myocardial I/R. Methods Left anterior descending coronary artery ligation was used to induce models of myocardial I/R in mice. The I/R mice were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 42 publications
(73 reference statements)
0
22
0
Order By: Relevance
“…as an essential member of the seven categories of the sirtuin protein family, SirT1 is considered as a critical regulator of cell apoptosis and autophagy (45). recently, numerous studies reported that SirT1 was involved in myocardial i/r injury (46,47). ding et al (48) demonstrated that mir-29a inhibition could activate SirT1, thus preventing i/r injury by inhibiting oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…as an essential member of the seven categories of the sirtuin protein family, SirT1 is considered as a critical regulator of cell apoptosis and autophagy (45). recently, numerous studies reported that SirT1 was involved in myocardial i/r injury (46,47). ding et al (48) demonstrated that mir-29a inhibition could activate SirT1, thus preventing i/r injury by inhibiting oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…16 Increasing evidence supports a protective role of SEV in myocardial I/R injury. 17,18 The current study was designed to investigate specific molecular mechanisms with the previous finding that SEV is protective against myocardial I/R injury. 4 Also, SEV post-conditioning treatment has been noted to alleviate hypoxia-reoxygenation injury in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that SIRT1 attenuates nasal polypogenesis through EMT suppression ( 48 ). Furthermore, it has been demonstrated that SIRT1 is a target gene of miR-155-5p ( 49 ). Huang et al ( 49 ) reported that miR-155 downregulation stimulated cardioprotection against myocardial ischemia/reperfusion injury by binding to SIRT1.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that SIRT1 is a target gene of miR-155-5p ( 49 ). Huang et al ( 49 ) reported that miR-155 downregulation stimulated cardioprotection against myocardial ischemia/reperfusion injury by binding to SIRT1. However, the role of miR-155-5p in inhibiting EMT has not been extensively reported.…”
Section: Discussionmentioning
confidence: 99%